Traditional Socio-Political Structure & Institutions for Self-Governance of Paudi Bhuyan Tribe: An Ethnographic Study (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
The current paper examines the traditional socio political structure of the Paudi Bhuyan tribe in Odisha. In tribal communities, socio-political institutions are essential for sustaining peace, order, and stability. Various forms of socio-political l structures can still be observed at different levels, including bands, tribes, and chiefdoms. Among the Paudi Bhuyan, these socio-political institutions effectively manage socio-cultural, economic, religious, and local common property resources. The introduction of the Panchayati Raj Institution (PRI) system has led to modifications in the traditional council's dynamics. Over time, the role and status of the village head (Pradhan) have diminished with the election of ward members, sarpanchs and other PRI members. Historically, this socio-political institutions has played a vital role in socializing community members to uphold a dignified existence while ensuring order and peace within their locality.